Red Nightmare - Waggner, George (United States : Warner Brothers, 1962)
US anticommunist propaganda film, produced for the Department of Defence by Warner Brothers, dealing with the nightmare of a small-town American who finds his community taken over by communists.
Keywords: Propaganda films